Evaluation of risk factors for acute stroke using combined CTA and MR HR-VWI imaging - Chen, Lin; Guo, Qian; Zhao, JiXiu; Bao, Haihua; Meng, FanYin; Meng, Li (Frontiers in Neurology, 2025)
ObjectiveTo investigate the correlation between the changes of peripheral carotid fat density (PFD), the occurrence of acute cerebral ischemia events and the characteristics of different dangerous plaques.MethodsA retrospective analysis was performed on patients diagnosed with carotid plaque by head and neck CTA in the Affiliated Hospital of Qinghai University from January 2021 to March 2023. All patients received head magnetic plain scan, DWI and high resolution vascular wall imaging (MR HR-VWI). According to DWI images, the patients were divided into acute cerebral infarction group and non-acute cerebral infarction group, and the clinical data, CT features and PFD differences between the two groups were compared. Logistic regression analysis was used to adjust for confounding factors and calculate OR values. ROC curves were used to evaluate the predictive efficacy of symptomatic PFD, contralateral PFD and differential PFD for symptomatic and non-symptomatic carotid plaque. According to the CTA and MR HR-VWI, the patients were further divided into groups (calcification and non-calcification, ulcer and non-ulcer, intra-plaque bleeding and non-plaque bleeding, thin or broken fibrous cap and non-thin or broken fibrous cap, large lipid core and non-large lipid core). Multifactor linear regression equation was used to compare the differences of symptomatic side PFD, contralateral PFD and differential PFD among different groups, and to analyze the correlation between PFD and different plaque components. A retrospective analysis was conducted on patients diagnosed with carotid atherosclerotic plaques via head and neck CTA at Qinghai University Affiliated Hospital between January 2021 and March 2023. All patients underwent non-contrast brain MRI with diffusion-weighted imaging (DWI) and high-resolution vessel wall imaging (MR HR-VWI).Results(1) Clinical and Imaging Features: The acute stroke group demonstrated significantly elevated systolic (159.2 ± 28.35 vs. 143 ± 25.54 mmHg, p = 0.019) and diastolic blood pressures (93.67 ± 15.75 vs. 84.60 ± 13.21 mmHg, p = 0.016) compared to the non-acute group. Additionally, the acute stroke group exhibited greater plaque thickness (4.4 ± 1.4 vs. 2.9 ± 0.9 mm, p < 0.001), higher prevalence of severe stenosis (45.8% vs. 4.0%, p = 0.001), and more frequent ulcerated or irregular plaque surfaces (29.2% vs. 8.0%, p = 0.038). (2)Predictive Efficacy of PFD: In predictive analyses, symptomatic-side PFD showed superior performance in identifying acute ischemic events (AUC = 0.762, 95% CI: 0.653–0.870) compared to contralateral PFD (AUC = 0.672) and ΔPFD (AUC = 0.660). (3)Association with Plaque Components: Multivariate regression analysis revealed significant associations between symptomatic-side PFD and key plaque characteristics: intraplaque hemorrhage (IPH; β = 0.367, p < 0.001), lipid-rich necrotic core (LRNC; β = 0.190, p = 0.046), and plaque thickness (β = 0.225, p = 0.027). Notably, IPH exhibited the strongest correlation with PFD values among all evaluated components.ConclusionCarotid perivascular fat density (PFD) can be used as a potential imaging marker to evaluate the characteristics of local vascular inflammation and high-risk plaques, providing a new direction for the early diagnosis and targeted therapy of acute cerebral ischemic events.